Paremiologia e retorica epistolare: il proverbio nel «Salut d’amor» provenzale e francese (Carte Romanze, 2024)
The perusal of the texts that make up the corpus of troubadour love letters or salutz d’amor reconstructed to date documents how the use of proverbs and sententious expressions is firmly established in the tradition of the genre, although it has remained a little or not at all studied aspect until now. The paper proposes a preliminary investigation into the use of communis sententia according to the rules of the ars dictaminis produced between the 12th and 13th centuries, the erudite background of the Provençal genre (§ 1), with particular attention to the manuals and models of love epistolography (§ 1.1); it then provides a structured census of proverbs and sententiae in Occitan saluts (§ 4), analysing their formal characteristics, rhetorical connotation, and themes, between popular register and courtly source (§§ 2, 2.1, 2.2). The investigation is then extended to the corpus of French saluts (§ 3), in which the epistolographic model seems to disarticulate and with it also structures, thematic-rhetorical invariants and stylistic features typical of the salut, which appear less binding, in favour of a widespread adaptation to the narrative model, prevailing over the epistolary one. The evident reduction in the number of sententious and proverbial expressions in the French tradition of the salut can therefore be explained as an effect of the weakening of the stylistic-rhetorical markers of the epistle.
Keywords: troubadour poetry; medieval French poetry; salut d’amor; ars dictaminis; love epistolography; proverbs; proverbs and ars dictaminis; proverbs in troubadour literature; proverbs in French medieval literature